Isolation and biochemical characterization of a novel antimicrobial agent produced by Streptomyces violaceusniger isolated from Yemeni soil - Fathy, Shadia A.; Mohamed, Mohamed R.; Elhady, Mostafa M.; Al-habal, Mohamed H. (International Journal of Research in Medical Sciences, 2016)
Background: Infections caused by multidrug-resistant bacteria present daily challenges to infectious disease physicians in hospitals throughout the world and these pathogens are spreading into the community. The development of new antibacterial agents to combat worsening antibiotic resistance is still a priority area in anti-infective research. Methods: The experiments were carried out to search for new natural antibiotics through isolation of various Streptomyces strains from different soil samples from Yemen and studying the antimicrobial effects of metabolites that produced. In the same time, the toxicological and biochemical effects of the extracted antibiotic on animals were studied. Results: Streptomyces violaceusniger, was isolated from Yemeni soil sample produced active metabolite that was designated faqihmycin has substantial antimicrobial potential against different microbial species. Investigations into the possible mode of action of faqihmycin revealed that it affects cell wall synthesis and intracellular macromolecule contents of the Gram-positive bacteria Bacillus subtilis. Toxicity studies of faqihmycin confirmed the hepatotoxicity of faqihmycin, there is no strong evidence to suggest that it is nephrotoxic. Conclusions: Further studies with Faqihmycin are needed in order to elucidate its detailed mechanism of action on bacterial cells, as well as studies with Faqihmycin with different doses in order to determine its potential therapeutic use.